Integration-Ready Architecture and Design : Software Engineering with XML, Java, .NET, Wireless, Speech, and Knowledge Technologies - Zhuk, Jeff (Cambridge : Cambridge University Press, 2004)
What would you do if your IT job was no longer performed in your country? Your survival does not lie in limiting global collaborative engineering. IT workers will survive and prosper because of their ability to innovate, to quickly learn and change directions, and to evolve from Information Technology into Distributed Knowledge Marketplace. You have no choice but to be pro-active, learn to stay current, even run ahead of the game. Integration-Ready Architecture and Design bridges the gap for a new generation of wired and wireless software technologies and teaches a set of skills that are demanded by fast moving software evolution. This up-to-date textbook integrates theory and practice, going from foundations and concepts to specific applications. Through deep insights into almost all areas of modern CIS and IT, Zhuk provides an entry into the new world of integrated knowledge and software engineering. Readers will learn the 'what's, why's, and how's' on: J2EE, J2ME, .NET, JSAPI, JMS, JMF, SALT, VoiceXML, WAP, 802.11, CDNA, GPRS, CycL, XML, and multiple XML-based technologies including RDF, DAML, SOAP, UDDI, and WDSL. Students, architects, designers, coders, and even management benefit from innovative ideas and detailed examples for building multi-dimensional worlds of enterprise applications and creating distributed knowledge marketplace.
Title from publisher's bibliographic system (viewed on 28 Feb 2017).
Keywords: Software engineering; Expert systems (Computer science)